Dubin-Johnson Syndrome as Differential Diagnosis for Neonatal Cholestasis. Issue 5 (May 2021) - Junge, Norman; Goldschmidt, Imeke; Wiegandt, Jessica; Leiskau, Christoph; Mutschler, Frauke; Laue, Tobias; Ohlendorf, Johanna; Stalke, Amelie; Hartleben, Björn; Stindt, Jan; Keitel, Verena; Baumann, Ulrich; et al.
ABSTRACT: Objectives: Dubin-Johnson syndrome (DJS) is an autosomal recessive disorder in which multidrug-resistance-associated protein 2 (MRP2) deficiency causes an excretion disorder of conjugated bilirubin from hepatocytes into bile canaliculi. Its clinical presentation as neonatal cholestasis (NC) is rare but represents an important differential diagnosis. We aimed to define DJS-specific characteristics in NC, in particular in contrast to biliary atresia (BA) patients, and to highlight diagnostic tools that can help to avoid invasive diagnostic tests. Methods: We performed a review of case records from 2006 to 2020 and compared 4 DJS patients to 26 patients with proven BA consecutively diagnosed from 2014 to 2017. DJS was diagnosed by urine coproporphyrin analysis (UCA) and by genetic analysis (GA) for disease-associated ABCC2 variants. Results: Four male patients with NC were diagnosed with DJS by UCA and GA. DJS patients presenting as NC showed significantly lower values for aspartate aminotransferase (AST) ( P  < 0.001), for alanine aminotransferase (ALT) ( P  = 0.002) and for gamma-glutamyl transferase (GGT) ( P  < 0.001) compared with BA patients. Other examinations, however, could not clearly discriminate them (e.g.: stool colour, serum bile acids, total serum bilirubin). Conclusions: DJS is not only a rare differential diagnosis in NC with a suspicious phenotype (almost normal AST, ALT) but also shows overlapping features with BA. It should, therefore, be considered in every infant with NC and an atypical liver enzyme pattern to protect patients from unnecessary, invasive examinations. For this, UCA is a fast and reliable diagnostic tool. Confirmation based on GA is recommended. DJS patients have a good long-term prognosis. Abstract : Supplemental Digital Content is available in the text